Generalized pustular psoriasis with nail psoriasis in children: a case report - Gotama, Dewi; Sudarsa, Prima Sanjiwani Saraswati; Saputra, Herman (DiscoverSys Inc, 2019)
Background: Pustular psoriasis in children is one of the clinical variants of psoriasis. It is classified into generalized pustular psoriasis (GPP) and localized pustular psoriasis. The aetiology of psoriasis in children has not been known but is believed to be multifactorial. Nail psoriasis rarely occurs in children who suffer from skin psoriasis, with an incidence lower than that reported in adults. The diagnosis is generally made from the clinical and histological examination. The choice of therapy depends on the severity of the disease. Until now, there have been no specific guidelines for the management of psoriasis in children.Case report: A-15-years-old Balinese girl presenting with erythema, confluent scaly plaques over the trunk and extremities with pustules localized on the lower extremity. She had a history of fever before the lesions appear. Right third digital nails examination showed subungual hyperkeratosis and onycholysis. Positive auspitz sign and karsvlek phenomena were found. Biopsy result suitable for psoriasis. The patient got improvement after treated with methotrexate tablet orally and desoximetasone cream topically within four weeks without any side effect.Conclusion: Combination therapy with methotrexate tablet and desoximetasone cream give an effective result. However, the safety and side effects of methotrexate in children still need further monitoring.Ã‚Â